Environmental and Ambient Vibration Monitoring of Historical Adobe Buildings: Applications in Emblematic Andean Churches - Zonno, G.; Aguilar, R.; Boroschek, R.; Lourenço, P.B. (Taylor and Francis Ltd., 2021)
This paper presents the application of long-term environmental and structural remote monitoring in two emblematic 16th-century adobe churches located in southern Peru. The paper starts by presenting details of the planning and installation processes of the monitoring systems and continues with a detailed discussion of the results of almost two years of continuous monitoring. As expected, due to the large thermal inertia of the adobe systems and size of the buildings, the results of the environmental monitoring indicated a non-uniform distribution of temperature and relative humidity inside the buildings, and an important attenuation of the internal conditions in comparison with the external ones. On the other hand, the structural monitoring results evidenced an annual cyclical behavior of the natural frequencies with an apparent correspondence with the changes in environmental conditions due to seasonal influences. The correlation of ambient conditions and structural parameters confirmed the high affinity between relative humidity measurements and natural frequencies when hourly fluctuations were removed from the measurements. An important novelty is the affinity of structural dynamic properties and a single environmental variable, the absolute humidity, was also evidenced since high determination coefficients were obtained when it was compared with the identified natural frequencies.
Keywords: Adobe; Relative humidity; Natural (archaeology); Thermal inertia; Environmental science; Environmental monitoring; Humidity; Natural frequency; Vibration; Thermal; Remote sensing; Meteorology; Civil engineering; Engineering; Environmental engineering; Geography; Acoustics; Archaeology; Physics; https://purl.org/pe-repo/ocde/ford#2.01.04